"I was at the right place at the right time" The neglected role of happenstance in the lives of people and institutions - Armstrong, N; Agulnik, P (University of Chicago Press, 2020)
This paper presents coproduced ethnographic material concerning the development of mental healthcare services in Oxfordshire, UK. Our collaborative working method highlights arbitrary events and connections in both individual lives and in the lives of institutions. We introduce the analytic concept of happenstance to make sense of this. Happenstance helps us theorize how chance arises in particular social contexts, contains both randomness and patterning, and becomes entwined with agency. The notion of happenstance thus enables us to retain a sense that chance is social and makes links between individuals or institutions and their social surround independently of structuration or habitus. The anthropology of bureaucracy has focused on the clumsiness of institutional mechanisms and the strategies people adopt in response. We suggest a new angle, combining happenstance with Ian Hacking’s notion of “ecological niche” to suggest how an openness to happenstance might create a different kind of evolving institution.